2013
DOI: 10.5194/amt-6-1031-2013
|View full text |Cite
|
Sign up to set email alerts
|

Accurate measurements of carbon monoxide in humid air using the cavity ring-down spectroscopy (CRDS) technique

Abstract: Accurate measurements of carbon monoxide (CO) in humid air have been made using the cavity ring-down spectroscopy (CRDS) technique. The measurements of CO mole fractions are determined from the strength of its spectral absorption in the near-infrared region (~1.57 μm) after removing interferences from adjacent carbon dioxide (CO2) and water vapor (H2O) absorption lines. Water correction functions that account for the dilution and pressure-broadening effects as well as absorption line inte… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
55
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 24 publications
0
55
0
3
Order By: Relevance
“…The instruments of the NASA-ATTREX package most important for the present study consist of a fast UV photometer for measurement of ozone (Gao et al, 2012), a gas chromatograph (Unmanned Aircraft System Chromatograph for Atmospheric Trace Species -UCATS; Wofsy et al, 2011, andMoore et al, 2003) as well as a Picarro instrument (Harvard University Picarro Cavity Ringdown Spectrometer -HUPCRS; Crosson, 2008;Rella et al, 2013;Chen et al, 2013) to measure CH 4 , CO 2 , and CO, a whole-air sampler (GWAS; Schauffler et al, 1998Schauffler et al, , 1999 to analyze a large suite of stable trace gases, and a three-channel scanning limb mini-DOAS (differential optical absorption spectroscopy) instrument for spectroscopic detection of O 3 , NO 2 , BrO, OClO, IO, O 4 , O 2 , H 2 O vapor , H 2 O liquid , and H 2 O solid in the UV-visnear-IR spectral ranges (e.g., Weidner et al, 2005;Platt and Stutz, 2008;Kritten et al, 2010Kritten et al, , 2014Kreycy et al, 2013;Stutz et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The instruments of the NASA-ATTREX package most important for the present study consist of a fast UV photometer for measurement of ozone (Gao et al, 2012), a gas chromatograph (Unmanned Aircraft System Chromatograph for Atmospheric Trace Species -UCATS; Wofsy et al, 2011, andMoore et al, 2003) as well as a Picarro instrument (Harvard University Picarro Cavity Ringdown Spectrometer -HUPCRS; Crosson, 2008;Rella et al, 2013;Chen et al, 2013) to measure CH 4 , CO 2 , and CO, a whole-air sampler (GWAS; Schauffler et al, 1998Schauffler et al, , 1999 to analyze a large suite of stable trace gases, and a three-channel scanning limb mini-DOAS (differential optical absorption spectroscopy) instrument for spectroscopic detection of O 3 , NO 2 , BrO, OClO, IO, O 4 , O 2 , H 2 O vapor , H 2 O liquid , and H 2 O solid in the UV-visnear-IR spectral ranges (e.g., Weidner et al, 2005;Platt and Stutz, 2008;Kritten et al, 2010Kritten et al, , 2014Kreycy et al, 2013;Stutz et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…The Picarro analyzer uses wavelength-scanned cavity ringdown spectroscopy (WS-CRDS) technology to make high-precision measurements of greenhouse gases (Crosson, 2008;Rella et al, 2013;Chen et al, 2013). HUPCRS reports concentrations of CO 2 , CH 4 , and CO every ∼ 2.2 s and the data are averaged to 10 s. In-flight precision for CH 4 is 0.2 ppb in 10 s. Briefly, the analyzer uses three distributed feedback (DFB) diode lasers in the spectral region of 1.55 to 1.65 µm.…”
Section: Ch 4 Measurements By Hupcrsmentioning
confidence: 99%
“…ments tested provide water vapor measurements and a correction function to transfer wet ambient air measurements to the dry mole fraction. This correction accounts for dilution and spectroscopic effects such as pressure broadening (Chen et al, 2013). In this study, we test the water vapor correction applied by the manufacturer of the different instruments.…”
Section: Water Vapor Correctionmentioning
confidence: 99%
“…The mean biases are nearly the same or smaller than the WMO-recommended limits of 2 ppb for CH 4 and 0.1 ppb for N 2 O, but the standard deviations are still relatively large compared to the mean values when several outliers with larger errors by the GC analyses were omitted. and Chen et al (2013) reported that the difference between the continuous (CRDS) and flask (GC/FID) aircraft measurements for CH 4 showed a small bias of 0.4 ± 1.3 ppb during their field intercomparisons. Our results are consistent with these previous studies showing that the bias in measuring CH 4 mole fraction by our WS-CRDS analyzer is smaller than the WMO's interlaboratory compatibility goal.…”
Section: Isotope Effect and Intercomparisonmentioning
confidence: 99%